Cardiovascular-kidney-metabolic progression associated with major adverse liver outcomes: mediating roles of plasma metabolites - Liang, Jingjing; Liang, Yongqi; Chen, Liwen; Cai, Mengyi; Li, Shuxian; He, Lige; Xu, Yining; Tan, Yilan; Li, Linna; Wu, Xianbo; Zou, Mengchen (Frontiers in Nutrition, 2025)
ObjectivesPrevious research has not yet established whether and how cardiovascular-kidney-metabolic (CKM) syndrome progression affects liver outcomes.MethodsThis prospective study utilized data from the UK Biobank (UKB) cohort, including 415,713 individuals without prevalent liver diseases or substance use disorder. The CKM syndrome stages were defined according to the Presidential Advisory from the American Heart Association. Outcomes were major adverse liver outcomes (MALOs), including hospitalization for metabolic dysfunction-associated steatotic liver disease (MASLD), severe liver disease (SLD), and liver-specific mortality. Cox proportional hazards models examined the association between CKM stages and MALOs. The CMAverse R package was used to investigate the potential mediating effects of plasma metabolomic data.ResultsAfter multivariable adjustment, a higher CKM stage was associated with elevated risks of incident MASLD hospitalization [hazard ratios (HRs) = 7.38, 95% confidence intervals (CIs): 4.34, 12.55], SLD hospitalization (HR = 3.46, 95% CI:1.94, 6.16), and liver-specific mortality (HR = 4.35; 95% CI: 1.38, 13.69). CKM components were, respectively, and cumulatively associated with MALOs (all p < 0.05). Mediation analyses indicated that tyrosine partially mediated the associations between CKM stage and MASLD-related hospitalization (7.62%), SLD-related hospitalization (9.46%), and liver-related death (11.19%), while linoleic acid-to-total fatty acids ratio partially mediated MASLD hospitalization (41.18%), SLD hospitalization (34.30%), and liver-related death (45.17%) (all q < 0.001).ConclusionCKM progression elevates MALO risk, partially mediated by amino acids and fatty acids. These findings identify high-risk patients who may benefit from targeted liver surveillance for secondary prevention of CKM syndrome.